ANALISA MENU ENGINEERING “BEVERAGE” DI MOMOO JUICE BAR & COFFEE WINDSDOR KOTA BATAM - Jeheil Lontaan; Dailami; Wahyudi Ilham; Syailendra Reza Irwansyah Rezeki (JURNAL MENATA, 2022)
A food and beverage business requires a product to sell, namely a menu, a menu needs to be evaluated periodically to find out if the menu has increased or decreased. This study aims to determine the advantages and popularity of a menu using Menu Engineering theory and data processing with qualitative data as support. Menu Engineering theory uses 2 techniques, namely Menu Mix and Contribution Margin. This study provides results from 81 drink menus offered by MoMoo Juice Bar and Coffee Windsor, there are 28 menus or 34.57% in the star category, 13 menus or 16.05% in the plowhorse category, 21 menus or 25.93% in the category puzzle, and 19 menus or 23.46% in the dog category. Evaluation of the menu according to the classification is highly recommended to the management to increase business profitability.